A vendor's evaluation–using AHP for an Indian steel pipe manufacturing company - Giridhar Kamath; Rakesh Naik; H C Shiva Prasad (International Journal of the Analytic Hierarchy Process, 2016)
To improve a firm's supply chain performance, it is essential to have a vendor evaluation process to be able to showcase an organization's success in the present aggressive market. Hence, the process of evaluating the vendor is a crucial task of the purchasing executives in supply chain management. The objective of this research is to propose a methodology to evaluate the vendors for a steel pipe manufacturing firm in Gujarat, India. For the purpose of the study, the Analytical Hierarchy Process was used to evaluate the best raw material vendor for this company. Multiple qualitative and quantitative criteria are involved in the vendor evaluation process. To solve the complex problem of vendor evaluation, a trade-off between these multi-criteria is important. The outcomes indicated that the AHP technique makes it simpler to assign weights for the different criteria for evaluating the vendor. Research findings showed that quality is the most important criterion followed by delivery, cost and vendor relationship management.
Keywords: C44; M11; 330; Cost; Delivery; Quality; Vendor evaluation; Vendor relationship management